STUDY EKOLOGI HUBUNGAN IKLIM DENGAN KEJADIAN MALARIA DI KOTA BENGKULU TAHUN 2011-2013 - Gustina, Mely (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
Malaria is one of spread diseases becoming a society problem both in International andIndonesia. Bengkulu city is one of malaria endemic areas. The purpose of this study is to know thecorrelation between climate (temperature, rainfall, and wind speed) and malaria cases in Bengkulucity in the year 2011-2013. The result of this study showed that connective variable in malaria case israinfall with total of rain in value (r = - 0,349 and p = 0,037 < α = 0, 05). It can be concluded thatthere are relationship between total rainfalls with malaria cases, and there are relationship betweentotal of rain days with malaria cases.